Polymeric Micelles as Carriers for Nerve-Highlighting Fluorescent Probe Delivery - Hackman, Kayla M. (Mol Pharm, 2015)
[Image: see text] Nerve damage during surgery is a common morbidity experienced by patients that leaves them with chronic pain and/or loss of function. Currently, no clinically approved imaging technique exists to enhance nerve visualization in the operating room. Fluorescence image-guided surgery has gained in popularity and clinical acceptance over the past decade with a handful of imaging systems approved for clinical use. However, contrast agent development to complement these fluorescence-imaging systems has lagged behind with all currently approved fluorescent agents providing untargeted blood pool information. Nerve-specific fluorophores are known, however translations of these agents to the clinic has been complicated by their lipophilic nature, which necessitates specialized formulation strategies for successful systemic administration. To date the known nerve-specific fluorophores have only been demonstrated preclinically due to the necessity of a dimethyl sulfoxide containing formulation for solubilization. In the current study, a polymeric micellar (PM) formulation strategy was developed for a representative nerve-specific fluorophore from the distyrylbenzene family, BMB. The PM formulation strategy was able to solubilize BMB and demonstrated improved nerve-specific accumulation and fluorescence intensity when the same fluorophore dose was administered to mice utilizing the previous formulation strategy. The success of the PM formulation strategy will be important for moving toward clinical translation of these novel nerve-specific probes as it is nontoxic and biodegradable and has the potential to decrease the necessary dose for imaging while also improving the safety profile.